Legal Remedies for Preventing Uncertified Vessels: Following Their Expertise for Shipping Safety - Muhammad Nurzaman Firdaus; Dewi Asri Puannandini; Fahmi Ali Ramadhani (Universitas Islam Nusantara, 2022)
Shipping safety is very important and occupies a central position in all aspects of the shipping world. Aspects inherent in shipping safety include characteristics, attitudes, values, and activities regarding how important it is to meet safety and security requirements related to transportation in waters and ports. Shipping safety in Indonesia, especially when many crew members do not have certificates according to their expertise or are fake affects the safety of the skipper, the crew, and the passengers or goods they carry because it will have a negative impact. This research method was carried out using a Normative Juridical approach because in this study the source of legal material for laws and regulations. The method used is a method of approaching laws that are carried out by reviewing the laws and regulations handled. This study takes the example of a case regarding the forgery of a Level IV Nautical Expert Certificate based on the decision of the Subang District Court Number: 246/Pid.B/ 2020/ PN.Sng by a defendant named Sakban (57) who was proven to have forged a Level IV Nautical Expert Certificate in 2016 and was caught in 2020. The results of his research are the consequences caused by ship crews who do not have a certificate of expertise under their expertise can affect the safety of their voyages themselves if there are many crew members and ship captains who are not competent in their fields. There is also still weak supervision carried out by law enforcement officials and kesyahbandar to prevent the rampant forgery of expertise certificates, especially for the crew and the skipper, so there are many loopholes for perpetrators of forgery of expertise certificates, especially in the shipping world.